2014
DOI: 10.1016/j.bbrc.2014.05.100
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular pH in sperm physiology

Abstract: Intracellular pH (pHi) regulation is essential for cell function. Notably, several unique sperm ion transporters and enzymes whose elimination causes infertility are either pHi dependent or somehow related to pHi regulation. Amongst them are: CatSper, a Ca2+ channel; Slo3, a K+ channel; the sperm-specific Na+/H+ exchanger and the soluble adenylyl cyclase. It is thus clear that pHi regulation is of the utmost importance for sperm physiology. This review briefly summarizes the key components involved in pHi regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
139
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(146 citation statements)
references
References 139 publications
(163 reference statements)
0
139
1
2
Order By: Relevance
“…Therefore, we investigated if an alkalinization could mimic these responses. We found that a 10 mM NH 4 Cl addition evoked a [Ca 2+ ]i increase in sperm head and flagellum (Fig. 6A).…”
mentioning
confidence: 77%
See 3 more Smart Citations
“…Therefore, we investigated if an alkalinization could mimic these responses. We found that a 10 mM NH 4 Cl addition evoked a [Ca 2+ ]i increase in sperm head and flagellum (Fig. 6A).…”
mentioning
confidence: 77%
“…To allow comparison and averaging independent spermatozoa, BCECF and Fluo-4 data were equally treated and normalized using the maximal value obtained with NH 4 Cl or ionomycin, respectively, per ROI. In BCECF/Fluo-4 parallel measurements, fluorophores were distinguished according to the cell response to NH 4 Cl or ionomycin, which were added consecutively at the end of each experiment. As chemotaxis occurs during the first 3 s of the speract response [3], only the first 3 s of the pHi response were used for the kinetic analysis.…”
Section: Image Processing and Data Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Noncapacitated epididymal murine spermatozoa are slightly depolarized at about −40 mV, however they hyperpolarize up to −60 mV upon capacitation [137]. This effect is attributed to potassium permeability and two members of the Slo family of potassium channels have been recently proposed to play a role in this process [21,25,26,29,31,33,[138][139][140][141]. Slo3 (Kcnu1), a pH-sensitive, calcium-independent and weakly voltage-sensitive channel, has been identified as the principal potassium channel in murine sperm [25,26,29,31,33,[141][142][143].…”
Section: Potassium Channels Of Spermmentioning
confidence: 99%